2018
DOI: 10.1021/acs.jced.7b00770
|View full text |Cite
|
Sign up to set email alerts
|

Vapor–Liquid Equilibrium of Ethyl Lactate Highly Diluted in Ethanol–Water Mixtures at 101.3 kPa. Experimental Measurements and Thermodynamic Modeling Using Semiempirical Models

Abstract: A thermodynamic study of the vapor−liquid equilibrium for the ternary system ethyl lactate−ethanol−water was performed at 101.3 kPa and infinite dilution regarding ethyl lactate, for boiling temperatures ranging from (352.3 to 370.0) K. The experimental measurements were carried out with a recirculation still and the equilibrium compositions of ethyl lactate were determined by gas chromatography. The volatility of ethyl lactate decreases when the ethanol content in the liquid phase is increased. The investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 63 publications
3
9
0
Order By: Relevance
“…In equilibrium, the monomer species, I or J (= A , B , C ), could form association complexes in the vapor or liquid phase, and the mixture could include monomers ( I 1 ), dimers ( I 2 ), and trimers ( I 3 ), which have been authenticated according to the aforementioned theoretical studies. As some examples of this behavior, ethanoic acid is considered to exist as a dimer and tetramer in the vapor phase, while the other group presumes that only dimer and trimer are formed . Moreover, homodimers, trimers, tetramers, and heterodimers were assumed to exist in the propanoic acid system, and water exists in the forms of dimer, trimer, tetramer, and even higher polymers. However, we have confirmed that not only monomer, homodimer, and homotrimer exist in the vapor and liquid phase but also heterodimerization occurs between two species I and J ( I ≠ J ), The maximum number of heterodimers M in the system of N components is given by Moreover, we have corroborated that heterotrimerization could take place between two species I and J ( I ≠ J ), No much higher complexes are verified according to the theoretical studies mentioned above. The maximum number of heterotrimers S in the system of N components is manifested similarly, The number of components found in the mixture could be different from the apparent N where the first, second, and third terms refer to all of the possible monomers, heterodimers, and heterotrimers, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In equilibrium, the monomer species, I or J (= A , B , C ), could form association complexes in the vapor or liquid phase, and the mixture could include monomers ( I 1 ), dimers ( I 2 ), and trimers ( I 3 ), which have been authenticated according to the aforementioned theoretical studies. As some examples of this behavior, ethanoic acid is considered to exist as a dimer and tetramer in the vapor phase, while the other group presumes that only dimer and trimer are formed . Moreover, homodimers, trimers, tetramers, and heterodimers were assumed to exist in the propanoic acid system, and water exists in the forms of dimer, trimer, tetramer, and even higher polymers. However, we have confirmed that not only monomer, homodimer, and homotrimer exist in the vapor and liquid phase but also heterodimerization occurs between two species I and J ( I ≠ J ), The maximum number of heterodimers M in the system of N components is given by Moreover, we have corroborated that heterotrimerization could take place between two species I and J ( I ≠ J ), No much higher complexes are verified according to the theoretical studies mentioned above. The maximum number of heterotrimers S in the system of N components is manifested similarly, The number of components found in the mixture could be different from the apparent N where the first, second, and third terms refer to all of the possible monomers, heterodimers, and heterotrimers, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The aroma compounds considered are ethanal 8 and ethyl lactate. 40 This latter study was carried out by the same authors of this paper.…”
Section: Compilation and Thermodynamicmentioning
confidence: 88%
“…Specific measurements for ternary systems have also been reported. The aroma compounds considered are ethanal and ethyl lactate . This latter study was carried out by the same authors of this paper.…”
Section: Compilation and Thermodynamic Modeling Of Vapor–liquid Equil...mentioning
confidence: 97%
See 1 more Smart Citation
“…The UNIQUAC model requires the volume, r i , and surface area q i, parameters for each pure component i . In this study, for EL and water, the values were taken from the literature, and for organic salts, the values were calculated, and they are presented in Table S4. According to the UNIQUAC model, the six parameters obtained from the experimental LLE data, Δ u ij , and the corresponding root-mean-square deviation of the composition, σ x , are given in Table .…”
Section: Resultsmentioning
confidence: 99%